Microbial community‐assisted water quality control and nutrients recovery: emerging technologies for the sustainable development of aquaponics. Issue 8 (10th June 2019) - Yang, Limin; Chen, Fufeng; Xiao, Yan; Li, Huankai; Li, Jun; Leng, Lijian; Liu, Hui; Zhong, Yuming; Li, Kun; Lu, Qian; Zhou, Wenguang
Abstract: Aquaponics is considered as a possible method to produce aquatic animals and plants in an environmentally‐friendly way, but its commercialization is seriously hindered owing to some technical and economic problems. Recently, the integration of microbial community with aquaponics is on the way to becoming the next‐generation technology for the sustainable development and commercialization of the aquaponics industry. This article provides an authoritative discussion on the novel microbial community‐assisted aquaponics, which will be emerging from the research environment to industrial application in the coming future. Principles and key technologies of this novel aquaponics, as well as the potential challenges to its commercialization, are discussed. It is expected that the emerging technologies discussed in this work could address the existed technical problems and further promote the commercialization of aquaponics. © 2019 Society of Chemical Industry